Peran Self-efficacy dan Career Adaptability Sebagai Pemediasi Antara Pengaruh Protean Career Orientation Terhadap Keputusan Karir - Windari, Ratna Tri; Lestari, Wuryaningsih Dwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Technological developments and advances have brought about changes that require individuals to not only have relevant technical skills but also a high level of adaptability in order to maintain and develop their careers. This study aims to explore how protean careers, career adaptability, and self-efficacy in career decision-making interact among young people aged 14-27 years in Karanganyar Regency. The sample consisted of 240 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using the SEM method with Smart PLS. The results show that Protean Career Orientation has a positive and significant effect on Career Decisions, Self-Efficacy, and Career Adaptability. Career Adaptability positively and significantly influences Career Decisions, while Self-Efficacy does not influence Career Decisions. Overall, Protean Career Orientation influences Career Decisions through Adaptability, but not through Self-Efficacy.